Theoretical and Practical Premises in Building Up the Health Public Policies in the Field of Transplant - Cristina GAVRILUŢĂ (Transylvanian Review of Administrative Sciences, 2013)
The existing data at European level situate Romania on the last places regarding the rate of organ donation. This fact is also an indicator of the effect of the health policies in Romania in the field of transplant. The research carried out (the study on the population’s attitudes towards the organ donation, the study on the theme of organ transplantation as presented in the Romanian media, and the study on the opinions of the ER doctors, neurologists and neurosurgeons regarding the organ donation and transplantation) show different models of approaching the issue of transplant in the European area. The investigations carried out among doctors identify a series of issues which relate, on the one hand, to the cultural component, and, on the other hand, to the structure and functioning of the Romanian health system. The survey carried out in Iași in 2012 shows favorable attitudes towards organ donations in the conditions of a lack of information and of a less effective policy regarding organ donation.